2013
DOI: 10.1111/geb.12084
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of parasite island syndromes without long‐term host population isolation: parasite dynamics in Macaronesian blackcaps Sylvia atricapilla

Abstract: AimThe study of parasite biogeography on islands is important for our understanding of both the processes involved in the evolution of parasite assemblages worldwide and the ecology and conservation of insular communities. By studying the haemosporidian blood parasites of a bird that has recently colonized a number of oceanic islands, we were able to test hypotheses relating to the processes of parasite colonization and community assembly prior to the permanent isolation of host species on islands.Location The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 44 publications
2
56
3
1
Order By: Relevance
“…This suggests that, as predicted by island biogeography theory (MacArthur & Wilson, 1967), a broad ecological niche would be selected as a strategy that decreases the chances of extinction – in this case of parasites colonizing a new area where potential host populations are small (Beadell et al , 2006). The same pattern was also found for the Haemosporidian parasites of a songbird in the Madeira and the Canary islands (Pérez-Rodríguez et al , 2013). …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This suggests that, as predicted by island biogeography theory (MacArthur & Wilson, 1967), a broad ecological niche would be selected as a strategy that decreases the chances of extinction – in this case of parasites colonizing a new area where potential host populations are small (Beadell et al , 2006). The same pattern was also found for the Haemosporidian parasites of a songbird in the Madeira and the Canary islands (Pérez-Rodríguez et al , 2013). …”
Section: Discussionsupporting
confidence: 75%
“…As generalist parasites are considered poor competitors (Hellgren et al , 2009), an increase of co-infections on islands could play a role in limiting parasite densities and prevalence. Previous studies on the prevalence of blood parasites on islands were inconclusive, with either higher (Illera et al , 2015) or lower prevalence on islands (Pérez-Rodríguez et al , 2013). These conflicting results may arise from the fact that parasite prevalence is also likely to vary in relation to environmental and local factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the generally low prevalence and diversity of the hemosporidian parasites on islands (Hellgren, Križanauskienė, Hasselquist, & Bensch, ; Martínez‐de la Puente et al, ; Padilla, Illera, Gonzalez‐Quevedo, Villalba, & Richardson, ; Pérez‐Rodríguez, Ramírez, Richardson, & Pérez‐Tris, ; Sari, Klompen, & Parker, ) and the presence of only one potential vector species on the island, we expected to find an essentially simple host‐vector‐parasite system. However, we found that the opportunistic feeding behavior of louse flies resulted in an unexpected massive transmission of haemosporidians from kills to falcons’ louse flies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, limited contact between expanded‐ and historical‐range populations, and low densities of expanded‐range populations, could foster escape from natural enemies, including parasites (Phillips et al ., ), such as that observed in species that naturally colonize islands (e.g. see Güoy de Bellocq et al ., ; Pérez‐Rodríguez et al ., ). Additionally, parasites often require different host species in sequence to complete their life cycles, and some of the required host species may be absent or less abundant in expanded ranges: a pattern observed for parasites of invasive species.…”
Section: Introductionmentioning
confidence: 97%